Schedule Acceleration Planning in Construction Project (Case Study: Japek II Selatan Tollroad) - Aziz Irsyad; Ika Arum Puspita; Wawan Tripiawan (International Journal of Innovation in Enterprise System, 2022)
This study focuses on the remaining work at stations (STA) 53+950 to 54+550 in Jakarta – Cikampek II Selatan Toll Road Package III project to find the critical path, completion durations, and project costs before and after acceleration. The CPM Technique was used to compile network planning diagrams, determine the critical path and project duration. Crashing Project was applied to crash schedule through the total project duration and cost whose changes due to the implementation of the crashing method. The critical path was found in mobilization, tree felling, clearing, dig and haul, borrow material, subgrade preparation, base course (A grade), subbase course (B grade), drainage layer, lean concrete (t=10 cm), concrete pavement, concrete barrier type B, and signage. In the CPM, the duration of project completion is 214 days. The total project budget under normal circumstances is Rp22.073.412.654. After accelerating with the Crashing Project by proposed overtime was obtained the reduced total cost of Rp32.004.882 from the total normal cost of Rp22.073.412.654 to Rp22.041.407.771 with an optimum duration of 183 days.